2023
DOI: 10.2217/rme-2023-0042
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Osteoarthritis Severity, BMI and Age on Clinical Efficacy of Bone Marrow Aspirate Concentrate in the Treatment of Knee Osteoarthritis

Abstract: Aim: The aim of this study was to assess whether BMI, severity of knee osteoarthritis, age and gender have any influence on the final clinical results of bone marrow aspirate concentrate injection. Method: A total of 111 study participants with painful knee osteoarthritis and different characteristics concerning before mentioned factors underwent bone marrow aspirate concentrate (BMAC) therapy and were followed up for 1 year. Result: Significant pain and functional improvement were observed in all participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This was confirmed in a study of 111 participants by Rasovic, who reported, that participants' age and BMI did not influence the clinical outcome, but there was an influence of OA severity, especially among older patients. His study shows that BMAC therapy is effective and he states, that younger patients with milder OA changes could be better candidates for long-lasting and more efficient BMAC therapy 39 www.nature.com/scientificreports/ with grade I to grade IV degenerative arthritis of the knee and confirmed this findings, that a BMAC injection significantly improved both knee pain and functions in the patients with degenerative arthritis of knee. Also, the injection would be more effective in early to moderate phases 40 .…”
Section: Discussionmentioning
confidence: 74%
“…This was confirmed in a study of 111 participants by Rasovic, who reported, that participants' age and BMI did not influence the clinical outcome, but there was an influence of OA severity, especially among older patients. His study shows that BMAC therapy is effective and he states, that younger patients with milder OA changes could be better candidates for long-lasting and more efficient BMAC therapy 39 www.nature.com/scientificreports/ with grade I to grade IV degenerative arthritis of the knee and confirmed this findings, that a BMAC injection significantly improved both knee pain and functions in the patients with degenerative arthritis of knee. Also, the injection would be more effective in early to moderate phases 40 .…”
Section: Discussionmentioning
confidence: 74%
“…His study shows that BMAC therapy is effective and he states, that younger patients with milder OA changes could be better candidates for long-lasting and more e cient BMAC therapy. 39 Kim assessed the outcome of BMAC injection in patients with grade I to grade IV degenerative arthritis of the knee and con rmed this ndings, that a BMAC injection signi cantly improved both knee pain and functions in the patients with degenerative arthritis of knee. Also, the injection would be more effective in early to moderate phases.…”
Section: Discussionmentioning
confidence: 83%
“…The results showed that BMAC injection effectively improved pain in knee OA patients with short-to mid-term follow-up 15 . A recent study by Rascovic et al (2023) involving 111 patients also showed that BMAC therapy is effective, especially for younger patients with milder OA 16 . The combination of intra-articular and subchondral BMAC injection can provide clinical and imaging benefits for up to 24 months in patients with knee OA 17 .…”
Section: Bone Marrow Aspirate Concentratesmentioning
confidence: 93%